The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s001140100249
|View full text |Cite
|
Sign up to set email alerts
|

Fungal bioturbation paths in a compact disk

Abstract: We report here on bioturbation traces, with micro-dendrite textures, composed of a mixture of altered aluminum and polycarbonate, which have been developed in a common compact disk (CD), destroying information pits. Fungal hyphae proliferated in these deteriorated zones, and Geotrichum-type fungus was isolated from surface-sterilized CD fragments. The severe biodeterioration described is attributed to the slow growth of this arthroconidial fungus on the CD material in the tropical indoor environment of Belize,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
3
8
0
Order By: Relevance
“…1a), similar to that reported in the original CD found in Belize (García-Guinea et al, 2001). After 6 months of incubation, at room temperature and high humidity, the biodeterioration path in the CD-A was clearly visible to the naked eye (Fig.…”
Section: Reproduction Of the Fungal CD Alterationsupporting
confidence: 86%
See 3 more Smart Citations
“…1a), similar to that reported in the original CD found in Belize (García-Guinea et al, 2001). After 6 months of incubation, at room temperature and high humidity, the biodeterioration path in the CD-A was clearly visible to the naked eye (Fig.…”
Section: Reproduction Of the Fungal CD Alterationsupporting
confidence: 86%
“…In the area colonized by the fungus, mobilization of the reflective metal and removal of the phthalocyanine dye present in the data-recording layer were observed. Similar degradation ways have been found in CDs from other tropical countries although the responsible organisms have not been studied (García-Guinea et al, 2001). It has been reported that basidiomycetes fungi, including different Bjerkandera P. Karst.…”
Section: Reproduction Of the Fungal CD Alterationsupporting
confidence: 52%
See 2 more Smart Citations
“…Also, photographic materials, binders, and supports can be made of plastics (12). Plastic audiovisual material, including compact discs, can be subject to biodeterioration (25). Initial fungal colonization of plastics in audiovisual materials generally means failure because of interruption of the signal, whereas further colonization could lead to degradation of the plastics themselves (7,43).…”
Section: Biodeterioration Of Objects Made Of Plasticsmentioning
confidence: 99%